2005
DOI: 10.1111/j.1469-7580.2005.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact guidance in human dermal fibroblasts is modulated by population pressure

Abstract: Morphogenesis is underpinned by orientated cell division, motility and growth. The substratum for migrating cells in vivo comprises either extracellular matrix or the surfaces of adjacent cells and both are believed to inform the dynamic behaviour of adherent cells through contact guidance. Collisions between migrating cells in vitro can induce the phenomena of contact inhibition of locomotion and division, suggesting that their sensitivity to substratumderived cues may also be influenced by population density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
2
33
0
1
Order By: Relevance
“…According to this model, any cue for fibroblast alignment may subsequently cause collagen alignment. In vitro studies have shown that fibroblasts will align in the direction of uniaxial mechanical stretch (Eastwood et al, 1998;Wang & Grood, 2000;Neidlinger-Wilke et al, 2001;Raeber et al, 2008;Hsu et al, 2009;Steward et al, 2010;, in the direction of aligned matrix fibers or micropatterned ridges (Guido & Tranquillo, 1993;Sutherland et al, 2005;Doyle et al, 2009;Sun et al, 2010), and in the direction of chemokine gradients (Knapp et al, 1999;Grinnell et al, 2006;Melvin et al, 2011). Mechanical, structural, and chemical cues are all present during infarct healing, which makes all of them potential determinants of infarct collagen alignment.…”
Section: Fibroblasts Mediate the Development Of The Mechanical Propermentioning
confidence: 99%
See 2 more Smart Citations
“…According to this model, any cue for fibroblast alignment may subsequently cause collagen alignment. In vitro studies have shown that fibroblasts will align in the direction of uniaxial mechanical stretch (Eastwood et al, 1998;Wang & Grood, 2000;Neidlinger-Wilke et al, 2001;Raeber et al, 2008;Hsu et al, 2009;Steward et al, 2010;, in the direction of aligned matrix fibers or micropatterned ridges (Guido & Tranquillo, 1993;Sutherland et al, 2005;Doyle et al, 2009;Sun et al, 2010), and in the direction of chemokine gradients (Knapp et al, 1999;Grinnell et al, 2006;Melvin et al, 2011). Mechanical, structural, and chemical cues are all present during infarct healing, which makes all of them potential determinants of infarct collagen alignment.…”
Section: Fibroblasts Mediate the Development Of The Mechanical Propermentioning
confidence: 99%
“…We obtained cell alignment data from 8 studies that plated cells on substrates with micro-ridges of varying height and pitch (Clark et al, 1990;Sutherland et al, 2005;Loesberg et al, 2005Kim et al, 2009;Pot et al, 2010;Sun et al, 2010;. The axis of cell alignment (mean angle) was parallel to the axis of ridge alignment.…”
Section: Structural Guidance Cuementioning
confidence: 99%
See 1 more Smart Citation
“…[ nd wood-base 171,172] In thes retrieve the lo g the shape o plied in the d stem [174] [178] avy objects a low fuel elcro TM was tures of the m, using the adable from he National Mainly, the interactions between cells and surface occur through contact guidance, a locomotor response of cells depending on the surrounding environment micro-and nano-characteristics given not only by the tissue matrices [179] but also by the presence of other cells. [180] In mid 1990s it has been shown that almost all mammalian cells respond to the tissue topography activating different cellular behaviors. [181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198] For example, various experiments showed that cells adhere onto nano-grates and align along the direction of the grating.…”
Section: Instructive Factors In Tissuesmentioning
confidence: 99%
“…Various stimuli are proposed to have a role in instructing cellular differentiation, such as the stiffness and topography [175][176][177][178][179] of the tissue interstitial matrix or the physical contact with other cells present in the tissue. [180] It has been demonstrated in vitro that specific characteristics of biomaterials, for example the surface stiffness or topographical features (e.g. tips or grooves), [185][186][187][188][191][192][193][194][195][196][197] allow the control of stem cell fate.…”
Section: Introductionmentioning
confidence: 99%